2009
DOI: 10.1186/1757-7241-17-12
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of controlled studies: do physicians increase survival with prehospital treatment?

Abstract: Background: The scientific evidence of a beneficial effect of physicians in prehospital treatment is scarce. The objective of this systematic review of controlled studies was to examine whether physicians, as opposed to paramedical personnel, increase patient survival in prehospital treatment and if so, to identify the patient groups that gain benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 41 publications
(135 reference statements)
2
64
0
Order By: Relevance
“…Accurate triage and bypass protocols (whereby patients with major trauma are taken directly to a major trauma centre, potentially bypassing closer EDs) are therefore essential [3,46,67,68]. Helicopter transfer to definitive care has recently been demonstrated to reduce mortality from major trauma [69], but this is in addition to evidence that physicians bring survival benefits to the pre-hospital phase of trauma care [70,71].…”
Section: Pre-hospital Carementioning
confidence: 99%
“…Accurate triage and bypass protocols (whereby patients with major trauma are taken directly to a major trauma centre, potentially bypassing closer EDs) are therefore essential [3,46,67,68]. Helicopter transfer to definitive care has recently been demonstrated to reduce mortality from major trauma [69], but this is in addition to evidence that physicians bring survival benefits to the pre-hospital phase of trauma care [70,71].…”
Section: Pre-hospital Carementioning
confidence: 99%
“…In summary, there is no existing evidence to support paramedic-delivered pre-hospital critical care for patients with OHCA, while for physician-delivered pre-hospital critical care studies have shown mixed results, 15 with the largest and most recent study failing to demonstrate any benefits. 21 Currently, all EMS in the United Kingdom (UK) dispatch ALS trained paramedics to confirmed or suspected OHCA.…”
Section: Introductionmentioning
confidence: 98%
“…14 A systematic review by Botker from 2009 examined the effect of physician-delivered pre-hospital critical care on OHCA outcomes and found a benefit, 'based on limited evidence'. 15 Small sample size, 16 comparison of pre-hospital critical care with very limited basic life support 17 and study designs which did not control for significant confounding factors [17][18][19][20] make the application and generalisation of these findings problematic.…”
Section: Introductionmentioning
confidence: 99%
“…1e4 Increase survival rate is more common in traumatic patients who received pre-hospital care. 4 For non-traumatic conditions, patients with some particular diseases have been shown to benefit from pre-hospital treatment, such as chronic obstructive pulmonary disease (COPD) or myocardial infarction. 3,4 The Thai government established the pre-hospital emergency medical service in 2008 to improve emergency medical care.…”
Section: Introductionmentioning
confidence: 99%
“…4 For non-traumatic conditions, patients with some particular diseases have been shown to benefit from pre-hospital treatment, such as chronic obstructive pulmonary disease (COPD) or myocardial infarction. 3,4 The Thai government established the pre-hospital emergency medical service in 2008 to improve emergency medical care. The patients can reach the pre-hospital medical care by calling a toll-free number (1669) which will connect them to the nearest hospital.…”
Section: Introductionmentioning
confidence: 99%